SERAT WULANG PUTRA SEBAGAI SUMBER PENDIDIKAN KARAKTER GENERASI MODERN (Serat Wulang Putra As a Source of Characters Education for Modern Generation) - Nugroho, Yusro Edi; Widodo, Widodo; Hardyanto, Hardyanto (Balai Bahasa Jawa Tengah, 2019)
Javanese people in the past used piwulang text as a source of behavior. Javanese identity is inherent in conduct and behavior. They believe that the Javanese teachings possess valuable values and character. The purpose of this study is to present the Serat Wulang Putra (SWP) as a source of character education for the modern generation. The Javanese text is one of the sources of character education based on Indonesian culture. This type of research is qualitative research focussing on character education designedt and applied to the modern generation. This research is a descriptive qualitative one. The theory applied in this research is content analysis theory. Serat Wulang Putra (SWP) text is analyzed in order to obtain some values that are useful for modern generation character educations, namely mutual respect, obedience to teachers, obedience to parents, toughness, honesty, responsibility, steadfastness, wisdom, patience, love and care, and carefulness. Keywords: Javanese Piwulang (teaching), character education